Local ATP generation by brain-type creatine kinase (CK-B) facilitates cell motility. - Jan W P Kuiper; Remco van Horssen; Frank Oerlemans; Wilma Peters; Michiel M T van Dommelen; Mariska M te Lindert; Timo L M ten Hagen; Edwin Janssen; Jack A M Fransen; Bé Wieringa (PLoS ONE, 2009)
BACKGROUND: Creatine Kinases (CK) catalyze the reversible transfer of high-energy phosphate groups between ATP and phosphocreatine, thereby playing a storage and distribution role in cellular energetics. Brain-type CK (CK-B) deficiency is coupled to loss of function in neural cell circuits, altered bone-remodeling by osteoclasts and complement-mediated phagocytotic activity of macrophages, processes sharing dependency on actomyosin dynamics. METHODOLOGY/PRINCIPAL FINDINGS: Here, we provide evidence for direct coupling between CK-B and actomyosin activities in cortical microdomains of astrocytes and fibroblasts during spreading and migration. CK-B transiently accumulates in membrane ruffles and ablation of CK-B activity affects spreading and migration performance. Complementation experiments in CK-B-deficient fibroblasts, using new strategies to force protein relocalization from cytosol to cortical sites at membranes, confirmed the contribution of compartmentalized CK-B to cell morphogenetic dynamics. CONCLUSION/SIGNIFICANCE: Our results provide evidence that local cytoskeletal dynamics during cell motility is coupled to on-site availability of ATP generated by CK-B.